(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
This study aims to formulate a herbal anti-acne gel containing extracts of Psidium Guajava and Tabernaemontana Divaricata and to characterize the formulated gel for its physicochemical properties. The extraction method used was maceration and Continuous hot extraction. The presence of diverse phyto-constituents in the obtained extracts was also determined. Three formulations containing the extracts of Psidium Guajava and Tabernaemontana Divaricata were prepared using 1% Carbopol 940 as a gelling agent. Parameters like colour, odour ,homogeneity, phase separation, consistency, washability, pH, viscosity, spreadability and anti-microbial activity were evaluated. The formulated gels were odourless, uniform, consistent, without lumps and washable. It was found that pH of the prepared formulations was closer to skin, had good viscosity and spreadability. The anti- microbial activity of the prepared gel formulation against p-acne was also investigated using disc diffusion method. The anti-microbial activity of the prepared gels was studied with a clear inhibition zone. The formulated gel F2 has greater anti-microbial activity with a larger diameter of zone of inhibition compared to F1 and F3. It was concluded from study that the extract of Psidium Guajava and Tabernaemontana Divaricata can be formulated in an aqueous gel-based system for topical therapy of acne vulgaris.